PERANCANGAN E-MODUL BERBASIS ANDROID UNTUK MEMFASILITASI PENINGKATAN KEMAMPUAN SPASIAL MATEMATIS SISWA SMP KELAS VIII PADA MATERI GEOMETRI - Husna, Laelatul; Khotimah, Khotimah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
The purpose of this study is to determine the feasibility, student responses, and improvement in spatial mathematical abilities through the use of an Android-based e-module for facilitating the spatial skills of eighth-grade students in geometry. This research is a development study using the R&D (Research and Development) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were eighth-grade students at SMP PGRI Kramatwatu. The research instruments included Android-based e-module evaluation sheets to assess the module's feasibility and student responses, as well as test instruments to measure students' spatial mathematical abilities. Based on the results, the Android-based e-module was considered highly feasible, with a material expert rating of 80.72% and a media expert rating of 82.5%, yielding an average score of 81.61%. The percentage of student responses in the limited trial was 78.83%, and in the field, trial was 77.09%, both falling under the "good" category, with an overall average of 77.96%. The improvement in students' spatial abilities, based on the normalized gain index, reached 0.58, classified as a moderate improvement